Naval shipboard communications systems - Kim, J. C. (John C.) (Prentice Hall PTR, 1995)
Naval communications is constantly evolving and adopting modern technology drawn from all aspects of engineering disciplines. This all-in-one reference is designed specifically for engineers who understand communications, but who need to become familiar with the specifics of U.S. Naval shipboard communications and methods. Explores, from a theoretical and practical engineering system level point of view, both external and intra-platform components - communication requirements, technical background for understanding the naval communications architecture, the communications subsystems used by the navy (from ELF to EHF), equipment for implementation, operation procedures, configuration control, and logistical support considerations. For engineers who understand communications, but who need to become familiar with the specifics of U.S. Naval shipboard communications and methods.